HUBUNGAN TIMBAL BALIK ANTARA MANUSIA DENGAN LINGKUNGAN DI TAMA NEW TOWN YANG TERCERMIN DALAM ANIME HEISEI TANUKI GASSEN “POMPOKO” KARYA TAKAHATA ISAO - CAHYANI, ANDRIA KUMALA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Human and nature have a mutual relation that both benefits and disrupting. Human utilizes natural resources to fulfill everyday needs. If Human continuously exploits nature without any concern for other forms of organisms, the results of it will be terrible for all living organisms. Nature can be a source of inspiration for creating many forms of art, such as poems, paintings, movies and animes (Japanese animation). One of the animes that covers the mutual relation between mankind and nature is entitled Heisei Tanuki Gassen Pompoko. This anime portrays the very relation between the two sides (mankind and nature) in a small town called “Tama New Town.” Therefore, in this research the writer will give a response to the formulation of the problem, which is how the relation between mankind and nature are portrayed in the anime. By utilizing the study of environmental literary criticism, this research will explain the reciprocal relation between mankind and nature that happens descriptively through text and pictures. The result of this research shows not only the beneficial side of the relation, but also the disrupting side as well, such as forest exploitation, environmental pollution and wild animal hunting. Aside from the entertainment purposes, anime can be used as a learning medium regarding sociocultural and environmental aspects of life. Therefore, the writer suggests to further analyze anime through different approaches, such as through the study of folklore to discover the role of tanuki in Japanese culture. Keyword: Ecocriticism,Tama New Town, Anime, Pompoko